Improving Stability of Anthocyanin Extracted from Ipomoea batatas by Co-pigmentation - Rachma Tia Evitasari; Gita Indah Budiarti (Eksergi, 2022)
Public awareness of the dangers of using synthetic dyes has started to boost the prestige of natural dyes. The limitation of natural dyes is one of the causes of the limited use of natural dyes commercially. This research utilized purple sweet potato (Ipomoea batatas L.) as a source of anthocyanins. The purpose of this study was the stabilization of anthocyanins from purple sweet potato through the co-pigmentation process. The first stage is the extraction of natural anthocyanin dyes from purple sweet potatoes using the microwave-assisted method, then stabilization of anthocyanins through a co-pigmentation process with variations in the addition of arabic gum, Fe-Alginate, and catechins at various concentrations as Total Anthocyanin Content (TAC), and stability test. The higher the concentration value of the co-pigmenting agent added to the extract, the higher the color shift, indicated by a decrease in the TAC value. The best copigmentation was obtained with green tea containing catechin concentration of 0.01 ml green tea/20 ml extract. with a TAC value of 0.1499 mg/L. Stabilization test against storage, co-pigmentation with catechins in green tea gave the best stability. While the stability against heating and oxidation, co-pigmentation with gum arabic will stabilize the condition of anthocyanin extracts.